2011
DOI: 10.1186/1471-2180-11-149
|View full text |Cite
|
Sign up to set email alerts
|

The conjugative plasmid of a bean-nodulating Sinorhizobium fredii strain is assembled from sequences of two Rhizobium plasmids and the chromosome of a Sinorhizobiumstrain

Abstract: BackgroundBean-nodulating Rhizobium etli originated in Mesoamerica, while soybean-nodulating Sinorhizobium fredii evolved in East Asia. S. fredii strains, such as GR64, have been isolated from bean nodules in Spain, suggesting the occurrence of conjugative transfer events between introduced and native strains. In R. etli CFN42, transfer of the symbiotic plasmid (pRet42d) requires cointegration with the endogenous self-transmissible plasmid pRet42a. Aiming at further understanding the generation of diversity am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Some authors emphasize the role of lateral genetic transfer in rhizobial evolution [39,40,[100][101][102][103], whereas others suggest the lateral transfer of nodulation genes occurred in minority of cases [104,105]. Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101]. There is an agreement, that (a) in numerous cases the world distribution of microsymbiont strains followed the distribution of their hosts, and the symbiosis-associated part of the genome (localized on symbiotic plasmid or symbiotic island) was subjected to the most intense evolution and fitting [103,104,106,107], and (b) other (non-symbiotic) parts of the rhizobial genome changed together with the symbiosis-related regions [105,108].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors emphasize the role of lateral genetic transfer in rhizobial evolution [39,40,[100][101][102][103], whereas others suggest the lateral transfer of nodulation genes occurred in minority of cases [104,105]. Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101]. There is an agreement, that (a) in numerous cases the world distribution of microsymbiont strains followed the distribution of their hosts, and the symbiosis-associated part of the genome (localized on symbiotic plasmid or symbiotic island) was subjected to the most intense evolution and fitting [103,104,106,107], and (b) other (non-symbiotic) parts of the rhizobial genome changed together with the symbiosis-related regions [105,108].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%
“…The frequency of plasmid transfer between rhizobial strains and the role of this genetic exchange in rhizobial evolution remains controversial [37][38][39][40]. However, the pool of plasmid replicons present in rhizobial cells is regarded as a (mostly) accessory genetic component which is evolving more rapidly than the chromosome [33], due to frequent changes (such as gene duplication, mutation or deletion) within particular replicons [41] or rearrangements between different replicons [42,43]. This distinction between the rhizobial chromosome and plasmids in the context of `evolutionary plasticity' and the role of these replicons in bacterial diversification resulted in the emergence of genomical concepts, which are similar to the pan-genome idea.…”
Section: Rhizobial Genomes -A Scheme For Extraordinary Strain Diversitymentioning
confidence: 99%
“…In many of these organisms, there is evidence that the chromosome and chromosome replicons coevolved with a shared evolutionary history and that the chromosome replicons were initially plasmids that did not carry any essential genes. The presence of multiple replicons in certain alphaproteobacteria is well known (11,12), and members of the Rhizobiaceae family contain a chromosome-like replicon of 3 to 4 Mb and multiple additional replicons (plasmids) that range in size from Ͻ100 kb to over 2 Mb (13)(14)(15)(16)(17)(18). In the root nodule bacteria, these plasmids were initially studied because they carried nodulation (nod) and nitrogen fixation (nif) genes.…”
mentioning
confidence: 99%
“…They are often maintained in the syntenic blocks and have a high level of nucleotide sequence identity among the homologous segments [55]. In Sfr GR64, a chimeric transmissible plasmid with segments from two Rhe plasmids and Sfr chromosome was detected [123]. The structural complexity and DNA sequence reiteration located in rhizobial extrachromosomal replicons could be one of the reasons of the tendency for genomic rearrangements.…”
Section: The Impact Of Postgenomic Knowledge To Rhizobial Plasmid Rolmentioning
confidence: 99%
“…In fact, some of these elements may be transferred to other bacterial cells by itself or in the presence of other mobilizing plasmids [73,92,110,111]. Cervantes et al [123] showed that Sfr plasmids might originate through the transfer of a symbiotic-conjugative-plasmid from the Rhe to a Sfr strain and at least two further recombination events among the Rhe plasmids and the Sfr genome. Recently, some (not only rhizobial) extrachromosomal replicons that have distinct properties from both chromosome and plasmids were reported and named "chromids" [128].…”
Section: The Impact Of Postgenomic Knowledge To Rhizobial Plasmid Rolmentioning
confidence: 99%